Effect of strength endurance exercises on developing the level of stabbing movement for fencing players - Ghaleb Oudah, Ishraq; Edan Muhammad, Huda (International Journal of Psychosocial Rehabilitation, 2020)
In order to reach advanced results in the game of fencing, we, as workers in the field of fencing, had to stand at some important points that should be available to every fencing player, and since this game is rich in its important and necessary skills and abilities, through which the player can win over her competition, it was definitely a focus on the most important strengths, highlighting and showing them distinctly and clearly, weaknesses, and their diagnosis in order to avoid any obstacle in the way of development and achievement. The stabbing movement is one of the basics of dueling, which requires the player to make a great effort at a specific time with the possibility of reaching the competitor’s goal in order to make a touch. This skill requires physical preparation Highly for their mastery and development through modern training curricula and various exercises, so they were exercises bearing strength, through which the player could face various resistances Which you encounter, whether in combat or training units with the same competence and ability while maintaining the stability of the level and not falling The research aims to prepare exercises for endurance and strength for the female athletes of the College of Physical Education and Sports Sciences team for girls. Identify the level of stabbing movement among the female athletes of the College of Physical Education and Sports Sciences for Girls. Know the effect of exercise holds the power to develop the level of appeal against the movement of the players elected College of Physical Education and Sports Science for Girls , was the use of the experimental method so as to suitability subject of the study, while the sample was players elected College of Physical Education and Sports Science for Girls of their number (16) player was selected purposively By (8) players in each group, the researchers prepared a set of exercises for strength endurance in the fencing game by (24) training units over a period of (8) weeks, at (3) training units per week at a rate of (90) minutes, while the time of the prepared exercises was (20) minutes of one training unit in the main section of the unit. The researchers concluded that endurance exercises have a positive effect on developing the level of stabbing movement in the experimental group. The two researchers recommend the necessity of using strength endurance exercises in the training units for fencing and in developing other abilities and skills.